Struggles for the human: Violent legality and the politics of rights - Coleman, Lara Montesinos (Durham, UK: London, UK: Duke University Press, 2024)
"Struggles for the Human is an ethical and political inquiry into human rights as a vocabulary of resistance. While contemporary legal scholars have critiqued human rights as an exclusionary concept that enables corporations and NGOs to mark certain subjects as deserving of rights and others as excluded from them, few have tracked the ways that grassroots organizations in the global south have used the notion of human rights to struggle against extractive capitalism. Based on historical research and Lara Montesinos Coleman's seventeen-year work alongside Colombia's internationalist Red de Hermandad (Network of Brother and Sisters), this study explores how grassroots groups have re-made human rights away from abstract universals, towards concrete struggles. Coleman shows how these struggles give rise to an "insurgent humanism," where what it means to be human is defined by the dialectical tension between a persistent critique of power relations and life-annihilating violence. Coleman tracks how neoliberalism's privatization of human rights has caused extraordinary repression and violence, as well how groups on the ground in Colombia have fought this privatization"--
Human Rights in Struggle -- Necroeconomics: Violence, Law, and Twenty-First-Century Plunder -- Deadly Colonial Ethics: Development Policy-Speak and Corporate Responsibility -- Privatizing Workers' Rights: Social Partnership in a Neoliberal World -- Elusive Justice: Capital, Impunity, and Counterlegality -- From Pernicious Optimism to Radical Hope: Human Rights beyond Abstract Values -- For an Insurgent Humanism -- What Do We Make of Human Rights? Ten Points.
Includes bibliographical references and index.
Keywords: Human rights; Political Science; Human rights -- Political aspects; Human rights -- Moral and ethical aspects; Protest movements; Neoliberalism; LAW / International; SOCIAL SCIENCE / Ethnic Studies / Caribbean & Latin American Studies